Paracoccidioidomycosis of the male genital tract. Report of eleven cases and a review of Brazilian literature - SEVERO, Luiz Carlos (2000)
Eleven cases of involvement of the genital tract in paracoccidioidomycosis were collected in a retrospective study of the clinical records of 683 patients seen in Porto Alegre, Rio Grande do Sul, Brazil. These cases are herein summarily reported. Eighteen similar cases were gathered in review of the Brazilian literature. Obtained data are discussed.